Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1994
DOI: 10.1007/bf00176434
|View full text |Cite
|
Sign up to set email alerts
|

HLA antigens and lymphocytes in proliferative vitreoretinopathy

Abstract: An immunohistopathological study was performed on 33 epiretinal membrane specimens obtained during vitreoretinal surgery from patients with rhegmatogenous retinal detachment complicated with proliferative vitreoretinopathy (PVR). Immunofluorescence and immunoperoxidase methods were used to detect major histocompatibility complex or HLA antigens and immunocompetent cells, and to identify the cellular and the extracellular component of the proliferative tissue. The following antigens were detected in epiretinal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
3
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 28 publications
2
3
0
Order By: Relevance
“…Immune responses following vitrectomy were not, however, limited to retina-intrinsic reactions. In accordance, previous studies have shown increased gliosis (GFAP-labeling) as well as increased presence of cellular antigens such as CD45 and CD68 in samples from patients with proliferative vitreoretinopathy (PVR) [45]. To explore the cellular involvement, we investigated three CD antigens with various roles in inflammation pathology.…”
Section: Discussionsupporting
confidence: 64%
“…Immune responses following vitrectomy were not, however, limited to retina-intrinsic reactions. In accordance, previous studies have shown increased gliosis (GFAP-labeling) as well as increased presence of cellular antigens such as CD45 and CD68 in samples from patients with proliferative vitreoretinopathy (PVR) [45]. To explore the cellular involvement, we investigated three CD antigens with various roles in inflammation pathology.…”
Section: Discussionsupporting
confidence: 64%
“…These findings are concordant with those of Ricker et al which reported that both CXCL10 and CCL11 levels were higher in patients who developed postoperative PVR [10]. In addition, several immunohistochemical studies have demonstrated the presence of macrophages and lymphocytes in PVR membranes, further confirming the crucial role of inflammation in the PVR process [19][20][21][22]41].…”
Section: Discussionsupporting
confidence: 91%
“…3,4 Multiple lines of evidence support an immunologic model for the development of PVR. Immune cells have been demonstrated in PVR specimens, [5][6][7][8] and several studies have demonstrated a role for inflammatory cell signaling molecules in the development of PVR. 1,2,[9][10][11] Banerjee et al 12 compared vitreous cytokine levels among patients with a variety of retinal conditions and demonstrated a complex pattern of mediator concentrations in patients with PVR.…”
mentioning
confidence: 98%